Effect of supplementation with barley and calcium hydroxide on intake of Mediterranean shrubs by goats - Rogosic, Jozo; Saric, Tomislav; Herceg, Nevenko; Zjalic, Slaven; Stanic, Svjetlana; Skobic, Dragan (ITALIAN JOURNAL OF ANIMAL SCIENCE, 2011)
Maquis plant communities are one of the most varied vegetation types in the Mediterranean region and an important habitat for wild and domestic herbivores. Although the majority of these shrubs are nutritious, the secondary compounds are the main impediments that reduce their forage value. In five experiments, we determined the effect of supplementing the diets of goats with calcium hydroxide plus barley and with barley alone on their intake of five dominant shrubs (Quercus ilex, Erica multiflora, Arbutus unedo, Viburnum tinus and Pistacia lentiscus) of the Mediterranean maquis community. The combination of calcium hydroxide plus barley and barley alone increased the utilisation of Q. ilex, E. multiflora and P. lentiscus, while the intake of A. unedo and V. tinus was not statistically significantly different. Calcium hydroxide and barley (energy) enhance the use of secondary compound-containing plants, which may increase the production of alternate forages and create a more diverse mix of plant species in the Mediterranean maquis plant community.
The following values have no corresponding Zotero field: pub-location: MEDITGROUP, VIA G BELLI, 4, PAVIA, 27100, ITALY publisher: PAGEPRESS PUBL
Keywords: barley; Calcium hydroxide; Food preference; Goat; Secondary compound

Growth performances , carcasses parameters and meat fatty acid composition of lamb fed green oak acorns ( Quercus ilex ) based diet - Keddam, Ramdane; Bouderoua, Kaddour; El-affifi, Mohamed; Attou, Ghalem Selselet- (African Journal of Biotechnology, 2010)
The aim of this experiment is to compare the effects of diets containing green oak acorns (GO) and barley (BL) on the growth performances, carcasses parameters and the composition in fatty acids of lambs. Two groups of five lambs each were fed, respectively, during 105 days with diets containing 50% of oaks acorns and 50% of barley. At the end of the test, the animals of the two diets expressed comparable body weights and weight gain. A significant difference (P < 0.05) was observed for the thickness of fat cover which is 3 mm for the BL group against 1.6 mm for GO group even if no significant difference was revealed concerning the output with slaughtering. The intramuscular lipids were significantly higher (P < 0.05) in the group of animals fed with GO diet compared to the BL diet (3.88 vs 2.83 g.100-1 g of muscle). Among the saturated fatty acids (SFA), the stearic acid significantly appeared in higher proportion (P < 0.05) in GO diet (20.8 vs 18.1%) whereas the palmitic acid is prevalent in the group of animals fed with the BL diet (25 vs 30%). For the polyunsaturated fatty acid (PUFA), no significant difference was observed between the two groups. The linoleic acid is prevalent among the PUFA of two groups without significant difference. The linolenic acid is higher in the animal fed BL. The n-6: n-3 ratio is higher in the BL group (8.9 vs 7.3). At the end, the low level of incorporation of PUFA in muscle of the lamb because of biohydrogenation, suggests us supplementing the diet by green grass.
Keywords: barley; fatty acid; lamb; meat; oak acorn